Understanding the emergence of the boson peak in molecular glasses - González-Jiménez, Mario; Barnard, Trent; Russell, Ben A.; Tukachev, Nikita V.; Javornik, Uroš; Hayes, Laure-Anne; Farrell, Andrew J.; Guinane, Sarah; Senn, Hans M.; Smith, Andrew J.; Wilding, Martin; Mali, Gregor; et al. (Nature communications, 2023)
A common feature of glasses is the “boson peak”, observed as an excess in the heat capacity over the crystal or as an additional peak in the terahertz vibrational spectrum. The microscopic origins of this peak are not well understood; the emergence of locally ordered structures has been put forward as a possible candidate. Here, we show that depolarised Raman scattering in liquids consisting of highly symmetric molecules can be used to isolate the boson peak, allowing its detailed observation from the liquid into the glass. The boson peak in the vibrational spectrum matches the excess heat capacity. As the boson peak intensifies on cooling, wide-angle x-ray scattering shows the simultaneous appearance of a pre-peak due to molecular clusters consisting of circa 20 molecules. Atomistic molecular dynamics simulations indicate that these are caused by over-coordinated molecules. These findings represent an essential step toward our understanding of the physics of vitrification. The ‘boson peak’ refers to an extra peak in the terahertz vibrational spectrum of glasses. It is now shown that for liquids of highly symmetric molecules the boson peak can be singled out by means of depolarized Raman scattering; the peak is linked to the formation of clusters of about 20 molecules.